2008
DOI: 10.1016/j.mod.2007.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal occlusion increases the rate of epithelial branching of embryonic mouse lung via the FGF10-FGFR2b-Sprouty2 pathway

Abstract: Tracheal occlusion during lung development accelerates growth in response to increased intraluminal pressure. In order to investigate the role of internal pressure on murine early lung development, we cauterized the tip of the trachea, to occlude it, and thus to increase internal pressure. This method allowed us to evaluate the effect of tracheal occlusion on the first few branch generations and on gene expression. We observed that the elevation of internal pressure induced more than a doubling in branching, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
76
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 35 publications
8
76
2
Order By: Relevance
“…Shaping these epithelial tissues requires the generation of forces transmitted between neighboring cells through intercellular polymers and molecular motors (Gorfinkiel and Blanchard, 2011;Kim and Davidson, 2011). The physical mechanisms that transmit and generate these forces include active changes in cell shape (often driven by apical actomyosin contractions) (Haigo et al, 2003;Dawes-Hoang et al, 2005), the addition or deletion of cells via division or apoptosis (Gong et al, 2004;BaenaLópez et al, 2005;Toyama et al, 2008;Tang et al, 2011), and passive stretching of the tissue in response to either intrinsic or extrinsic forces (Coulombre, 1956;Takeuchi, 1983;Unbekandt et al, 2008). Apical constriction is an active narrowing of cellular apices that is driven by a contractile actomyosin network, and these changes in cell shape can induce dramatic deformations of the tissue (Sawyer et al, 2010).…”
Section: Research Articlementioning
confidence: 99%
“…Shaping these epithelial tissues requires the generation of forces transmitted between neighboring cells through intercellular polymers and molecular motors (Gorfinkiel and Blanchard, 2011;Kim and Davidson, 2011). The physical mechanisms that transmit and generate these forces include active changes in cell shape (often driven by apical actomyosin contractions) (Haigo et al, 2003;Dawes-Hoang et al, 2005), the addition or deletion of cells via division or apoptosis (Gong et al, 2004;BaenaLópez et al, 2005;Toyama et al, 2008;Tang et al, 2011), and passive stretching of the tissue in response to either intrinsic or extrinsic forces (Coulombre, 1956;Takeuchi, 1983;Unbekandt et al, 2008). Apical constriction is an active narrowing of cellular apices that is driven by a contractile actomyosin network, and these changes in cell shape can induce dramatic deformations of the tissue (Sawyer et al, 2010).…”
Section: Research Articlementioning
confidence: 99%
“…A recent study showed that increasing the internal pressure in mouse lungs branching in culture by sealing the trachea, increases both proliferation and branching rates and that these changes are dependent on FGF10 signaling (Unbekandt et al, 2008). It has previously been speculated that the epithelial dilation phenotype of Fgf9 null lungs could result from a change in physical constraint on the epithelium due to mesenchymal thinning in the mutant, but this has not been tested (Colvin et al, 2001).…”
Section: Lung Progenitors and Branching Morphogenesismentioning
confidence: 99%
“…It has previously been speculated that the epithelial dilation phenotype of Fgf9 null lungs could result from a change in physical constraint on the epithelium due to mesenchymal thinning in the mutant, but this has not been tested (Colvin et al, 2001). Moreover, these authors suggest that Fgf9 and Fgf10 expression are normally regulated through changes in pressure (Colvin et al, 2001;Unbekandt et al, 2008). Such mechanical forces may be an important upstream regulator of both progenitor proliferation and morphogenesis, but this area of lung development is in much need of further study.…”
Section: Lung Progenitors and Branching Morphogenesismentioning
confidence: 99%
“…The earliest models focused on physical forces (reviewed by Lubkin, 2008), and combinations of experimental and computational studies have since confirmed that mechanical stress and internal pressure influence branching morphogenesis Nelson, 2010, 2012;Kim et al, 2013;Nelson and Gleghorn, 2012;Unbekandt et al, 2008;Varner and Nelson, 2014). WNT signaling affects the epithelial shape of new lung buds, but WNT signaling is not essential for lung branching morphogenesis and is thus not part of the core regulatory network (Kadzik et al, 2014).…”
Section: Introductionmentioning
confidence: 99%